Injury pain in track and field athletes: Cross-sectional study of mediating factors - Timpka, T.; Jacobsson, J.; Bargoria, V.; Dahlström, Ö. (Sports, 2019)
This exploratory study aimed to investigate whether data from track and field athletes support a conceptual model where the perception of pain affects self-evaluated health directly, yet is also indirectly mediated through personal factors and external stressors. A cross-sectional study was performed among athletes (n = 278) competing at the highest national level in the sport. Data for the dependent and independent variables were collected using the EuroQol-5 dimensions (EQ-5D) standardized measure of health status, and the mediator variables were collected by the Body Consciousness Scale (BCS-HA), Perceived Motivational Climate in Sport Questionnaire (PMCSQ), Commitment to Exercise Scale (CtES), and Brief Cope survey instruments. Two hundred and twenty-five (81%) athletes provided complete data sets. A strong direct association (c = -16.49; p < 0.001) was found between pain and self-estimated health, and a global mediation was found through the mediators (mediation effect (ME), -1.814, 90% confidence interval (CI), -3.414, -0.351). Specific mediation was observed for body competence (ME, -0.721; 90% CI, -2.028, -0.097) and private body consciousness (ME, -0.514; 90% CI, -1.761, -0.017). In conclusion, we found a negative association between perceived pain and self-evaluated health among competitive track and field athletes, and we found that a portion of the association was mediated through mediating factors. Under the assumption that the analyzed pain data primarily represented noxious pain, the conceptual model of the relationships between pain and self-estimated health among high-level track and field athletes was supported.